2018
DOI: 10.1016/j.jadohealth.2017.09.031
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Parental Notification Requirement on Illinois Minors' Access to and Decision-Making Around Abortion

Abstract: Illinois' PN requirement was associated with a decrease in the number of abortions among minors, delayed care for those from out-of-state, increased parental awareness of the pregnancy, and no change in parents' support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Finally, family structure (e.g., cohabitation) and parental characteristics (e.g., age and education of mother) differ significantly by geography and time, and these differences may affect child-parent relationships and the composition of teens at risk of being affected by PI laws. 2 Overall, there are ample 1 The literature consists of state-specific studies (Cartoof and Klerman 1986;Colman et al 2008;Ellertson 1997;Henshaw 1995;Kaestner 1996, 2001;Joyce et al 2006;MacAfee et al 2015;Ralph et al 2018;Ramesh et al 2016;Rogers et al 1991) and analyses using a broader set of states (Haas-Wilson 1996;Levine 2003;Myers and Ladd 2017;New 2011;Ohsfeldt and Gohmann 1994). After reviewing this literature, we conclude that results from these studies indicate that PI laws decreased abortions among minors and that an effect size of 15% is typical, although there is meaningful variation across studies.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, family structure (e.g., cohabitation) and parental characteristics (e.g., age and education of mother) differ significantly by geography and time, and these differences may affect child-parent relationships and the composition of teens at risk of being affected by PI laws. 2 Overall, there are ample 1 The literature consists of state-specific studies (Cartoof and Klerman 1986;Colman et al 2008;Ellertson 1997;Henshaw 1995;Kaestner 1996, 2001;Joyce et al 2006;MacAfee et al 2015;Ralph et al 2018;Ramesh et al 2016;Rogers et al 1991) and analyses using a broader set of states (Haas-Wilson 1996;Levine 2003;Myers and Ladd 2017;New 2011;Ohsfeldt and Gohmann 1994). After reviewing this literature, we conclude that results from these studies indicate that PI laws decreased abortions among minors and that an effect size of 15% is typical, although there is meaningful variation across studies.…”
Section: Introductionmentioning
confidence: 96%
“…1% from 1980 to 1982 (4,935 -3,942) / 4,935). 4 MacAfee et al (2015) and Ralph et al (2018) showed that abortions fell more among out-of-state minors following PI laws in New Hampshire and Illinois than among resident minors of each state. However, their results pertain to one clinic, or a few clinics, in close proximity to states without a PI law.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, about one in ten people endorsed the statement that they felt forced to disclose they were considering abortion and a similar proportion felt forced to wait to have the abortion after they had already made a decision. Research from Illinois found that enforcement of a parental notification law resulted in a slight increase in the proportion of young people who felt forced to have an abortion [51]. Our…”
Section: Discussionmentioning
confidence: 52%
“…In the current study, about one in ten people endorsed the statement that they felt forced to disclose they were considering abortion and a similar proportion felt forced to wait to have the abortion after they had already made a decision. Research from Illinois found that enforcement of a parental notification law resulted in a slight increase in the proportion of young people who felt forced to have an abortion [ 51 ]. Our findings suggest that mandatory waiting periods, parental involvement requirements, and other legal restrictions that reduce people’s autonomy around the pregnancy decision are likely to increase people’s psychosocial burden and their risk for experiencing mental health symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple studies examine changes in the number of abortions among adolescents after implementation of parental involvement laws [10][11][12][13], little is known about adolescents' experiences obtaining judicial bypass, particularly in the context of other abortion restrictions, and bypass' impact on their health. Absence of evidence on this topic is salient because such laws are justified on grounds of protecting adolescents from harm yet there is little evidence on consequences of these laws [14,15].…”
mentioning
confidence: 99%